BODY COMPOSITION AND BIOQUIMICAL PARAMETERS IN TYPE 2 DIABETICS - Cambri, Lucieli Teresa (2007)
The objective of this work was to verify the association between morphologic variables and biochemical parameters in type 2 diabetics. Twenty two voluntaries (54.2 ± 7.5 years) sedentary had been evaluated. The analyzed variable had been: body mass (BM), body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), percentage of body fat (%FB), fasting glucose (FG), total cholesterol (TC), triglycerides (TG), low density lipoprotein (LDL), high density lipoprotein (HDL) and glucosided hemoglobin (A1c). For the analysis of the results was used test T of Student, test U of Mann-Whitney, correlation of Pearson and Spearman' s Rank (p≤0,05). It was verified that 36.4% of the evaluated ones had been classified with overweight and 63.6% as obese. However, concerning to %FB, 89% had been classified as obese. It was verified that the group presents risk increased for chronic complications, since 90.9% of the individuals presented raised WHR, 63.6% elevated TC and 72.7% had presented TG above of normality. Additionally, 68.2% of the individuals presented the A1c above of 7%. Furthermore, partial correlation analyses demonstrated that majority of the analyzed morphologic variables are associated whit some parameters biochemical, indicators of the metabolic control in diabetic. In this way, the changes in the life style with more adequate diet, regular physical exercises and awareness of the importance of these cares for the health, are important to improvement of quality and/or length of life.